Switching from vitamin K antagonists to direct oral anticoagulants in non‐valvular atrial fibrillation patients: Does low time in therapeutic range affect persistence?. (23rd November 2021) - Toorop, Myrthe M. A.; Chen, Qingui; Kruip, Marieke J. H. A.; van der Meer, Felix J. M.; Nierman, Melchior C.; Faber, Laura; Goede, Lies; Cannegieter, Suzanne C.; Lijfering, Willem M.
Abstract: Background: Non‐valvular atrial fibrillation (NVAF) patients are advised to switch from a vitamin K antagonist (VKA) to direct oral anticoagulant (DOAC) when time in therapeutic range (TTR) is low. Objective: To examine if pre‐switch TTR determines persistence patterns in NVAF patients who are switched from a VKA to DOAC. Patients/Methods: Adult NVAF patients from three Dutch anticoagulation clinics who were newly switched from a VKA to DOAC between July 1, 2013 and September 30, 2018 were stratified by pre‐switch TTR levels. DOAC prescription records were examined to determine persistence patterns according to a 100‐day prescription gap. Cumulative incidences of non‐persistence to DOAC were estimated using the cumulative incidence competing risk method. The association of pre‐switch TTR levels with DOAC non‐persistence was evaluated by Cox regression models. Results: A total of 3696 NVAF patients were included, of whom 690 (18.7%) had a pre‐switch TTR ≤ 45%. After switching from VKA to DOAC, 14.0% (95% confidence interval [CI] 11.3–17.0%) of the patients with a pre‐switch TTR ≤ 45% became non‐persistent to DOAC within 1 year, while 9.8% (95% CI 8.7–11.0%) did in those with a pre‐switch TTR > 45%. In a multivariable model, a pre‐switch TTR ≤ 45% was associated with a higher risk of non‐persistence to DOAC (adjusted hazard ratio 1.55, 95% CI 1.22–1.97). Results were similar when using other cut‐off points (60% or 70%) to define a low TTR. Conclusion: NVAF patients switching from VKA to DOAC due to a low pre‐switch TTR saw a worse persistence pattern to DOAC after the switch compared to patients with a high pre‐switch TTR.